2012
DOI: 10.3109/10903127.2012.689931
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis Knowledge Among Paramedics: Results of a National Survey

Abstract: Whereas a large percentage of the paramedics recognized classic anaphylaxis, a very small percentage recognized atypical anaphylaxis. Less than half chose epinephrine as the initial drug of choice, and most respondents were unable to identify the correct route/location of administration. This survey identifies a number of areas for improved education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 10 publications
2
27
0
1
Order By: Relevance
“…17 That study was done at a single urban tertiary hospital receiving center. Our study is markedly different in that it covers two distinct geographic areas with multiple types of receiving hospitals (urban, suburban, teaching, HMO) and represents a dispatch area encompassing over 1455 square miles and 2.5 million people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 That study was done at a single urban tertiary hospital receiving center. Our study is markedly different in that it covers two distinct geographic areas with multiple types of receiving hospitals (urban, suburban, teaching, HMO) and represents a dispatch area encompassing over 1455 square miles and 2.5 million people.…”
Section: Discussionmentioning
confidence: 99%
“…A nationwide survey of paramedics showed that less than half of those who were able to recognize a classic case of anaphylaxis could correctly identify epinephrine as the primary drug of choice. 17 Even when epinephrine was correctly chosen as the drug of choice in simulated pediatric anaphylaxis cases, only half of the providers were able to give the appropriate dose and route. 18 A recent retrospective analysis of prehospital rates of epinephrine administration in an urban tertiary care pediatric ED demonstrated that among children with anaphylaxis, only 36% were given epinephrine by EMS providers prior to their arrival in the emergency department, findings largely consistent with an earlier retrospective study of epinephrine administration in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…Provider A drew 10 mL of epinephrine (10 mg) from the vial and delivered the second dose, which is more than 50 times greater than the correct dose. 15 Eighty-three percent had personally cared for an adult with anaphylaxis; 98% were confident that they could recognize anaphylaxis and 97% that they could manage it. Only 46% identified epinephrine as the initial drug of choice.…”
Section: Table 5 Synergistic Sequence Of Errorsmentioning
confidence: 99%
“…The simulated patient in this scenario met the diagnostic criteria for anaphylaxis: acute onset of illness with skin involvement (urticaria), respiratory involvement (wheezing and shortness of breath), and hypotension (>30% decrease in systolic blood pressure). 15,16 The child's length measured at the border of the white and blue color zone on the Broselow-Luten tape, which corresponded to an estimated weight of 18-19 kg. Hives were represented with circular, pink plastic bandages (see Figure 1).…”
Section: Study Protocol Simulationmentioning
confidence: 99%
“…In a blinded, cross-sectional online survey of a random sample of emergency medical service personnel, 99% of paramedics correctly identified a classic presentation of anaphylaxis; however, only 3% recognized an atypical presentation of anaphylaxis in a patient with abdominal pain, hypotension, and no skin signs [67]. …”
Section: Long-term Management: Self-treatment In Community Settingsmentioning
confidence: 99%